2020
DOI: 10.3390/cells9010158
|View full text |Cite
|
Sign up to set email alerts
|

Increased O-GlcNAcylation of c-Myc Promotes Pre-B Cell Proliferation

Abstract: O-linked β-N-acetylglucosamine (O-GlcNAc) modification regulates the activity of hundreds of nucleocytoplasmic proteins involved in a wide variety of cellular processes, such as gene expression, signaling, and cell growth; however, the mechanism underlying the regulation of B cell development and function by O-GlcNAcylation remains largely unknown. Here, we demonstrate that changes in cellular O-GlcNAc levels significantly affected the growth of pre-B cells, which rapidly proliferate to allow expansion of func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 44 publications
1
30
0
Order By: Relevance
“…Inhibition of O-GlcNAcylation by administration of OGT inhibitors downregulates the expression of c-Myc, cyclin A and cyclin E in a PD36 pre-B cell line. These results suggest that O-GlcNAcylation induces pre-B cells proliferation by increasing the expression of c-Myc and c-Myc downstream genes, such as cyclin A and cyclin E [151].…”
Section: Role Of O-glcnacylation In B Cellsmentioning
confidence: 75%
See 1 more Smart Citation
“…Inhibition of O-GlcNAcylation by administration of OGT inhibitors downregulates the expression of c-Myc, cyclin A and cyclin E in a PD36 pre-B cell line. These results suggest that O-GlcNAcylation induces pre-B cells proliferation by increasing the expression of c-Myc and c-Myc downstream genes, such as cyclin A and cyclin E [151].…”
Section: Role Of O-glcnacylation In B Cellsmentioning
confidence: 75%
“…Progenitor B cells undergo pro-B, early pre-B and late pre-B stages to become immature B cells in bone marrow. A recent study indicated that O-GlcNAcylation is increased in large pre-B cells and required for the proliferation of pre-B cells [151]. Inhibition of O-GlcNAcylation by administration of OGT inhibitors downregulates the expression of c-Myc, cyclin A and cyclin E in a PD36 pre-B cell line.…”
Section: Role Of O-glcnacylation In B Cellsmentioning
confidence: 99%
“…The collected voltage data were averaged and displayed on the LCD panel on the MCU board. In addition, to determine the availability of live cells for Shiga toxin detection, we performed tests on Gb3-expressing THP-1 and PD36 cells [22] (or parental cells not expressing Gb3, as negative controls) using poly-lysine. All measurements were repeated three times.…”
Section: Samples Preparation For Evaluationmentioning
confidence: 99%
“…Before stimulation, cells were incubated with RPMI-1640 containing only 10% fetal bovine serum. PD36 cells [22] were cultured in RPMI-1640 containing 10% fetal bovine serum, antibiotic-antimycotic, 0.1 mM MEM nonessential amino acids, 1 mM MEM sodium pyruvate, 55 μM 2-mercaptoethanol, and 2 mM L-glutamine. All cell culture was performed at 37˚C and 5% CO2 in a humidified incubator.…”
Section: Samples Preparation For Evaluationmentioning
confidence: 99%
“…Pro-oncogenic c-Myc controls cell proliferation, apoptosis, tissue remodeling, angiogenesis, cell metabolism, and the production of inflammatory and anti-inflammatory cytokines [16][17][18][19][20][21]. Steger et al [22] showed that the use of an antisense oligonucleotide against c-Myc in a mouse venous graft model involves a significant reduction in neointima formation in the postoperative period.…”
Section: Introductionmentioning
confidence: 99%